PENGARUH UMP (UPAH MINIMUM PROVINSI) RIIL DAN INVESTASI TERHADAP PRODUKTIVITAS TENAGA KERJA DI KALIMANTAN BARAT - B01108106, Danang Waskito (Jurnal Pembangunan dan Pemerataan, 2013)
This research was aimed to know the influence of minimum wage in province and investment toward labour in West Kalimantan in 1996 2011. This research was conducted in West Kalimantan with secondary data which source from West Kalimantan Center Agency on Statistics and Labour and Transmigration Service. Data was analyzed with ekonometrika model and using the Ordinary Least Square par by E-views 4.1. Base on estimate, that wage has a positive influence and no significant influence statisticaly to labour productivity in west Kalimantan. While statisticaly investment has a positive influence and significant toward labour productivity in west Kalimantan. Keyword : Minimum wage, Investment, Labor Productivity